From Social Isolation to Becoming an Advocate: Exploring Athletes' Grief Discourse About Lived Concussion Experiences in Online Forums. (October 2019) - Cassilo, David; Sanderson, Jimmy
Athletes who sustain concussions endure a variety of physical, mental, emotional, and social isolation effects as they rehabilitate. Accordingly, concussion recovery can induce grieving processes as athletes navigate the loss of athletic participation, social networks, and daily routine disruption. This research sought to gain a richer understanding of athletes' lived experiences with concussions through grief discourse shared in online narratives. Through an analysis of athletes' experiences shared via 58 blog posts on three concussion websites, the data reveal how athletes frame the losses that concussions bring into their lives, the subsequent feelings and expressions that result, along with how they eventually cope. The information disclosed in these online spaces can benefit parents, friends, coaches, and others to better understand concussion recovery, thereby enhancing their supportive communication and behaviors towards athletes as they rehabilitate from concussions.